Rice Husk Extract and Damar Resin as Corrosion Preventing Bio Coating Materials for Mild Steel in NaOH Solution - Pramudita, Marta; Novita, Lita; Ernawati, Hera; Hidayatullah, Andra; Pitaloka, A.B. (World Chemical Engineering Journal, 2022)
Corrosion is damage due to chemical reactions between metals or metal alloys with their environment. The use of coatings can reduce the rate of corrosion, but it is constrained by stability for a long time, so it is necessary to try other protections against mild steel that can cover the metal with a coating material. This research focuses on mild steel's bio coating expertise using 1M NaOH corrosive media using natural ingredients of rice husk extract and dammar resin. Rice husk and resin are plants that can be used as bio coating materials. Rice husk extract contains several compounds that can be used to inhibit the corrosion rate, one of which is silica. In contrast, dammar resin is a natural polymer with flexible and stable properties that can prevent corrosion. This study aimed to determine the effect of the components of the bio coating material (rice husk extract and dammar resin) on the ability to protect mild steel from 1M NaOH corrosive media by calculating the corrosion rate and efficiency of the bio coating material. There are five stages in the research: the sample preparation stage, the stage of making latex solutions, the stage of making bio coating products, the stage of metal coating with bio coating materials, and the inhibition efficiency testing phase. The method used is the weight loss method to determine the rate of corrosion formed. This study obtained the highest inhibition efficiency (IE%) of 83.23% at a bio coating concentration of 1500 ppm, with a temperature of 40˚C, and an immersion time of 1 hour.